Insight into the genomes of dominant yeast symbionts of European spruce bark beetle, Ips typographus - Cheng, Tian; Veselská, Tereza; Křížková, Barbora; Švec, Karel; Havlíček, Václav; Stadler, Marc; Kolařík, Miroslav (Frontiers in Microbiology, 2023)
Spruce bark beetle Ips typographus can trigger outbreaks on spruce that result in significant losses in the forest industry. It has been suggested that symbiotic microorganisms inhabiting the gut of bark beetles facilitate the colonization of plant tissues as they play a role in the detoxification of plant secondary metabolites, degrade plant cell wall and ameliorate beetle’s nutrition. In this study, we sequenced and functionally annotated the genomes of five yeasts Kuraishia molischiana, Cryptococcus sp., Nakazawaea ambrosiae, Ogataea ramenticola, and Wickerhamomyces bisporus isolated from the gut of Ips typographus. Genome analysis identified 5314, 7050, 5722, 5502, and 5784 protein coding genes from K. molischiana, Cryptococcus sp., N. ambrosiae, O. ramenticola, and W. bisporus, respectively. Protein-coding sequences were classified into biological processes, cellular and molecular function based on gene ontology terms enrichment. KEGG annotation was used to predict gene functions. All analyzed yeast genomes contain full pathways for synthesis of essential amino acids and vitamin B6, which have nutritional importance to beetle. Furthermore, their genomes contain diverse gene families related to the detoxification process. The prevalent superfamilies are aldo-keto reductase, ATP-binding cassette and the major facilitator transporters. The phylogenetic relationships of detoxification-related enzymes aldo-keto reductase and cytochrome P450 monooxygenase, and ATP-binding cassette are presented. Genome annotations also revealed presence of genes active in lignocellulose degradation. In vitro analyses did not confirm enzymatic endolytic degradation of lignocellulose; however, all species can utilize hemicellulose pectin and produce a large spectrum of exolytic enzymes attacking cellulose, chitin, and lipids.